Developing the KinkFinder for ILD* - Nakajima Jurina; Jeans Daniel (EPJ Web of Conferences)
This paper presents a study on kink reconstruction for long-lived particle (LLP) searches in the Time Projection Chamber (TPC) of the International Large Detector (ILD) at a future Higgs factory. We develop improved methods to reconstruct kinks’ position and associated track momenta, resulting in improved kink mass resolution. We study the perfomance for kinks from long-lived hadron decays inside the TPC.